THE USE OF NONVERBAL MEANS IN COMMUNICATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines how certain facial expressions influence the listener in the process of women’s communication, including in Internet texts. In women’s speech, visual contact, particularly eye contact, plays a significant role. Based on the Uzbek national mentality, women’s facial expressions reveal fear, excitement, respect, and modesty in interactions with representatives of the opposite sex.